Cardiovascular oncology: exploring the effects of targeted cancer therapies on atherosclerosis. Issue 5 (October 2018) - Seijkens, Tom T.P.; Lutgens, Esther
Abstract : Purpose of review: Targeted cancer therapies have revolutionized the treatment of cancer in the past decade, but cardiovascular toxicity is a rising problem in cancer patients. Here we discuss the effects of targeted cancer therapies on atherosclerosis. Increasing the awareness of these adverse effects will promote the development of evidence-based preventive strategies in the emerging field of cardiovascular oncology. Recent findings: Vascular endothelial growth factor inhibitors, immunomodulatory imide drugs, tyrosine kinase inhibitors and immune checkpoint inhibitors are successfully used as treatment for many types of solid and hematologic malignancies. However, clinical and experimental studies have demonstrated that these drugs can drive atherosclerosis, thereby causing adverse cardiovascular events such as myocardial infarction, stroke and peripheral arterial occlusive diseases. Summary: In this review, we discuss how on-target and off-target effects of novel cancer drugs may affect atherosclerosis and we postulate how these cardiovascular adverse events can be prevented in the future.